Amazing Facts Wild Animals: Go facts! - Aureole Publishing; Aureole Publishing (Aureole Publishing: UK, 2004)
How are lions and tigers similar and how are they different? How are penguin???s rescued after an oil spill? How do scientists get information about polar bears? Find out all this exciting facts and lots more in Amazing Facts-Wild Animals.
Lions and Tigers -- Family Life -- Grassland or Forest? -- Food.
Includes full-color illustrations and photographs.
Ages 7-10.
Text in English.
Hard binding.
Keywords: Wild Animals,Lions and Tigers, Polar Bears, -- Juvenile literature